Characterization of Chromosomal Instability in Murine Colitis-Associated Colorectal Cancer - Gerling, Marco (Public Library of Science, 2011)
BACKGROUND: Patients suffering from ulcerative colitis (UC) bear an increased risk for colorectal cancer. Due to the sparsity of colitis-associated cancer (CAC) and the long duration between UC initiation and overt carcinoma, elucidating mechanisms of inflammation-associated carcinogenesis in the gut is particularly challenging. Adequate murine models are thus highly desirable. For human CACs a high frequency of chromosomal instability (CIN) reflected by aneuploidy could be shown, exceeding that of sporadic carcinomas. The aim of this study was to analyze mouse models of CAC with regard to CIN. Additionally, protein expression of p53, beta-catenin and Ki67 was measured to further characterize murine tumor development in comparison to UC-associated carcinogenesis in men. METHODS: The AOM/DSS model (n = 23) and IL-10(−/−) mice (n = 8) were applied to monitor malignancy development via endoscopy and to analyze premalignant and malignant stages of CACs. CIN was assessed using DNA-image cytometry. Protein expression of p53, beta-catenin and Ki67 was evaluated by immunohistochemistry. The degree of inflammation was analyzed by histology and paralleled to local interferon-γ release. RESULTS: CIN was detected in 81.25% of all murine CACs induced by AOM/DSS, while all carcinomas that arose in IL-10(−/−) mice were chromosomally stable. Beta-catenin expression was strongly membranous in IL-10(−/−) mice, while 87.50% of AOM/DSS-induced tumors showed cytoplasmatic and/or nuclear translocation of beta-catenin. p53 expression was high in both models and Ki67 staining revealed higher proliferation of IL-10(−/−)-induced CACs. CONCLUSIONS: AOM/DSS-colitis, but not IL-10(−/−) mice, could provide a powerful murine model to mechanistically investigate CIN in colitis-associated carcinogenesis.